Strategic Planning for Sustainable Livelihoods of Local Communities in Areas Under Environmental Management, Case Study: Mote National Park and Wildlife Sanctuary - Mohammad Esmaeili; Hamid Reza Jafari (Sustainable Earth Trends)
Today, the livelihoods of many local communities on the edge of protected areas depend on the resources and ecosystem services of these areas. Given that protected areas, especially drylands, are vulnerable ecosystems due to limited resources and environmental pressures such as climate change and human disturbance, the use of protected areas' resources and ecosystem services is severely restricted. are faced with dealing with resources. Therefore, it is necessary to provide a specific sustainable livelihood diversification strategy to guide the cooperative protection of protected areas and the sustainable and reasonable use of the resources and services of these ecosystems by local communities and the beneficiaries of these areas. This study, using the Participatory Rural Assessment (PRA) method, identified and analyzed stakeholders and beneficiaries of Mote National Park and Wildlife Sanctuary. The identified stakeholders were then invited to a joint workshop to formulate strategies for sustainable livelihoods in the study area, and during the brainstorming and criteria weighted comparison matrix phases, the identified livelihoods were ranked and a diversification strategy for sustainable livelihoods was presented.